Bernard of Clairvaux and René Girard on desire and envy - Wharff, Jonah (Cistercian studies quarterly, 2007)
The article examines the understanding of human nature by French abbot Bernard of Clairvaux and professor René Girard. Bernard has derived his theory of human nature from Scripture. He stresses that individuals yearning for completeness is the result of being made in the image and likeness of God. On the other hand, Girard emphasizes that desire is mimetic, that another causes it. Bernard and Girard have expressed their views on how desire becomes misdirected which lead to envy.